2006
DOI: 10.1309/8fchq3vpbwm7b5x9
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Analysis of Peritoneal Mesothelioma and Primary and Secondary Serous Carcinoma of the Peritoneum

Abstract: The role of immunohistochemical markers in distinguishing peritoneal mesothelioma from primary or metastatic serous papillary carcinoma of the peritoneum was evaluated. We immunostained 20 peritoneal mesotheliomas (from 14 men and 6 women), 14 primary peritoneal carcinomas, and 14 metastatic serous ovarian carcinomas with a panel of 16 antibodies. Positive staining for calretinin was identified in 17 (85%) of 20 mesotheliomas, but all carcinomas were negative. Positive staining for Ber-EP4 was identified in 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
38
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 55 publications
4
38
0
2
Order By: Relevance
“…In contrast, ER and PR were reportedly negative in all malignant mesotheliomas of the peritoneum. 38,39 In this study, ER and PR were detected in 92 and 42% of papillary serous carcinomas of the ovary, respectively, similar to reported PAX2 in papillary serous carcinoma of the ovary G-X Tong et al findings. No ER or PR was detected in the 37 malignant mesotheliomas of the peritoneum in males that we studied.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, ER and PR were reportedly negative in all malignant mesotheliomas of the peritoneum. 38,39 In this study, ER and PR were detected in 92 and 42% of papillary serous carcinomas of the ovary, respectively, similar to reported PAX2 in papillary serous carcinoma of the ovary G-X Tong et al findings. No ER or PR was detected in the 37 malignant mesotheliomas of the peritoneum in males that we studied.…”
Section: Discussionsupporting
confidence: 89%
“…1 A number of comparative studies have been published in which the authors have attempted to determine the best panel of immunohistochemical markers that can assist in discriminating between peritoneal epithelioid mesotheliomas and serous carcinomas. [2][3][4][5][6][7][8][9][10] The recommended panels, however, have continually been subject to change as a result of the identification of new markers that can be used in the differential diagnosis of these tumors, as well as the publication of new information on the value of the individual markers. In a previous study by this author that was published in 2006 investigating the expression of a large number of positive mesothelioma markers (calretinin, podoplanin, keratin 5/6, and thrombomodulin) and positive carcinoma markers (MOC-31, Ber-EP4, BG-8 (Lewis y ), TAG-72 (B72.3), CD15 (leu-M1), and CA19-9), it was concluded that thrombomodulin, calretinin, and podoplanin were the best positive mesothelioma markers, and MOC-31 and Ber-EP4 were the best positive carcinoma markers for discriminating between peritoneal epithelioid mesotheliomas and serous carcinomas.…”
mentioning
confidence: 99%
“…Accordingly, the surface epithelium stains with vimentin, N-cadherin, calretinin, HBME1, CK7, and Ber-EP4 but it does not usually stain with CK20, and CA125 [1,3,9]. Besides, combinations of calretinin with Ber-EP4 as a marker of epithelial determinant which shows high expression in SC, and with ER that has an important role in the development of genital tract have been reported to be quite useful in the differential diagnosis of OSC with PMM [20][21][22][23]. In the study of Mozes, et al it has been reported that ER reactivity was demonstrated in 64.3% (36/56 cases) of OSC, 10.7% (4/37 cases) of ESC and 16.7% (1/6 cases) of TSC, whereas all PSC cases (5 cases) were negative [24].…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Mozes, et al it has been reported that ER reactivity was demonstrated in 64.3% (36/56 cases) of OSC, 10.7% (4/37 cases) of ESC and 16.7% (1/6 cases) of TSC, whereas all PSC cases (5 cases) were negative [24]. In particular, since Ber-EP4 is expressed in SCs in high levels, it is an important marker used in the differentiation of SC and PMM [20][21][22]25]. High rate of ER positivity is observed in OSC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation